Photocatalytic solution discoloration and self-cleaning by polyester fabric functionalized with ZnO nanorods. (May 2015) - Ashraf, Munir; Champagne, Philippe; Perwuelz, Anne; Campagne, Christine; Leriche, Anne
Polyester fabric was functionalized with ZnO nanorods grown by hydrothermal method. The ZnO seeds were deposited on fabric which provided the sites for growth of nanorods. The functionalized fabric showed self-cleaning by degrading color stains and solution discoloration under the effect of ultraviolet (UV) light which was studied using two azo and one triphenylemethylene dye. The stained fabric was exposed to UV light and K / S ( K = absorption coefficient, S = scattering coefficient) values were measured by spectrophotometer. Most of the stains were degraded in first 300 min and they disappeared completely after 24 h. The solution discoloration was studied by using different concentrations of dyes and was characterized by measuring absorbance. The rubbing and washing durabilities of the functionalized fabric were also investigated.